STATUS OF CHILDREN IN BLIND SCHOOLS IN THE NORTHERN AREAS OF PAKISTAN - Kazmi, Hasan Sajid; Shah, Ashfaq Ali; Awan, Abdul Aziz; Khan, Jaffar; Siddiqui, Noman (Journal of Ayub Medical College Abbottabad, 2007)
Background: Prevalence of blindness in Pakistan is estimated to be 0.9%, which comes to about 1.25 million persons. A significant number of these are persons under 20 years of age. To make these children useful citizens in future, special facilities are to be provided to these children for their education and training. A study was done to find out the visual status of the students studying in a blind school in Abbottabad, Pakistan, the only such facility in the region. Method: A total of 50 patients were examined during our visit to the blind school in Abbottabad. Age of the patients ranged from 6 to 27 years (mean: 12.32 years). All the students, who were otherwise healthy, were included in the study. Result: The most common disorder identified was malformed globe or traumatic eyes (16 cases, 32%), in most of the cases, leading to phthisis bulbi. Other conditions noticed were Retinitis Pigmentosa (10 cases, 20%), Keratoconus, Optic atrophy, Buphthalmos (6 cases each, 12%), corneal opacity (4 cases, 8%) and retinal detachment (2 cases 4%). Conclusion: We should work towards betterment of these schools by providing them with more funds, equipment and manpower. Regular visits of Ophthalmologists to these schools may be helpful. Genetic counselling should be arranged for the families. Key words: Blindness; Children; Cause; School.